Madurese Interference In An English Teacher’s Talk In A Senior High School In Bangkalan (RETAIN, 2014)
Madurese Interference In An English Teacher’s Talk In A Senior High School In Bangkalan Rona Ayu Putri Surya English Education, Languages and Arts Faculty, State University of Surabaya rona.ayuu@gmail.com Dosen pembimbing Ahmad Munir, S.Pd., M.Ed., Ph.D English Education, Languages and Arts Faculty, State University of Surabaya munstkip@yahoo.com Abstrak Penelitian ini mengkaji tentang berbagai interferensi (gangguan) dari bahasa pertama, dalam hal ini Bahasa Madura, dengan pengaruhnya terhadap bahasa yang digunakan seorang guru bahasa Inggris selama kegiatan belajar mengajar. Terdapat tiga rumusan masalah dalam penelitian ini, yakni: (1) Ucapan-ucapan mana saja dari teacher talk yang terpengaruhi oleh Bahasa Madura (2) Apa jenis interferensi yang mempengaruhi teacher’s talk, dan (3) Bagaimana pengaruh interferensi bahasa pertama guru terhadap pemahaman siswa pada teacher’s talk. Penelitian ini merupakan penelitian deskriptif kualitatif. Subyek dalam penelitian ini adalah seorang guru Bahasa Inggris dan siswa kelas X di salah satu Sekolah Menengah Atas di Bangkalan. Seluruh interaksi yang dilakukan guru dan murid selama proses belajar mengajar berlangsung direkam, ditranskip dan dianalisis untuk menemukan jawaban dari ketiga rumusan masalah. Hasil dari penelitian ini menunjukkan bahwa interferensi Bahasa Madura banyak ditemukan di fitur-fitur teacher talk tertentu yang paling sering digunakan oleh guru dan memberi kesempatan pada guru untuk sering berbicara selama kegiatan dikelas, seperti: referential question, display question, extended teacher turn, extended wait time, content feedback and confirmation check. Peneliti menemukan 92 interferensi dari Bahasa Madura, terdiri dari: 46 gangguan dalam struktur bahasa , 33 gangguan dalam fonologi and 13 dalam kata. Dapat disimpulkan bahwa interferensi Bahasa Madura ditemukan di beberapa ungkapan atau kalimat yang digunakan guru dalam fitur teacher talk. Jenis interferensi yang sering muncul adalah grammatical interference dan phonological interference. Interferensi dalam tatabahasa terjadi karena guru menggunakan struktur tatabahasa Bahasa Madura didalam berbahasa Inggris, sedangkan interferensi fonologi ditunjukkan oleh pelafalan kata dan intonasi guru yang . Interferensi-interferensi tersebut, kemudian, berdampak negatif pada pemahaman siswa terhadap teacher’s talk. Kata Kunci: interferensi bahasa, Bahasa Madura, teacher talk. Abstract This study is dealing with the variety of first language interference, in this case Madurese, with its typical influence on English teacher’s talk in classroom discourse Three research questions are formulated in this study, including: (1) which utterances of teacher talk are interfered by Madurese language, (2) what the types of interference have influenced the teacher talk, and (3) how the language interference in the teacher’s talk affects the students’ understanding. This research is designed in descriptive qualitative research. The subjects of this study are an English teacher and his students of X grade in one of Senior High School Bangkalan. All the interaction between the teacher and students during the teaching-learning process are recorded, transcribed, and analysed to find out the answers of three research questions. The result of this study shows that the Madurese interferences were dominantly detected in the certain teacher talk features which were mostly used by the teacher and gave the teacher chance to take up a major portion of talk in classroom interaction, such as: referential question, display question, extended teacher turn, extended wait time, content feedback and confirmation check. It was found there were 92 Madurese interferences, which 46 grammatical interferences, 33 phonological interferences and 13 lexical interferences. In conclusion, the Madurese interference was found in some utterances used in some teacher talk features. The types of interference which mostly appeared are grammatical interferences and phonological interference. The grammatical interference occurred when the teacher adopted the grammar structure of Madurese language to English, while the phonological interference is shown in the teacher’s pronunciation and intonation which indicated by characteristics of Madurese language. Those interferences, then, affect the students’ understanding toward the teacher’s talk in negative way. Keywords: language interference, Madurese language, teacher talk. INTRODUCTION Language is a media of communication that is used by teachers and their students to interact each other in the classroom discourse. According to Parrish (2004), the language that teachers use in class, or “teacher-talk,” can have a tremendous impact on the success of interactions they have with students. That because every single word the teacher said will determine how well they make their teaching, and guarantees how well students will learn. Except that, the classroom interaction can also enhance students’ understanding about the subject. they teach and how well the students learn. Thus, a teacher should choose the classroom language selectively in order to achieve the success of teaching-learning process. “A teacher’s voice is her essential realia. As with any other piece of valuable realia, it needs to be authentic, meaningful, engaging, and appropriate for learners”. (Weddel, 2008:3) Therefore, a teacher, especially an English Foreign Language (EFL) teacher, should notice her or his talk whether in vocabulary or language structures. But in fact, there are still many teachers that ignore that, they teach their learners without paying attention to their talk and learners’ understanding. As we know, basically, the foreign language teacher is also a learner. Although they are foreign language teachers, it does not cover the possibility that they also have done a mistake in producing target language since English is not her/his native language. As Ellis (1997) states that in second language acquisition often occurs some speaker’s errors and mistakes. A mistake that often occur in learning a new language is the learners always try to transfer directly the surface structures of L1 into L2 surface structures without paying attention to the second language rules (Dulay et.al, 1982). If the structures of the two languages are distinctly different, then one could expect a relatively high frequency of errors to occur in L2, thus indicating an interference of mother tongue on second language; this is most often discussed as a source of errors (negative transfer) (Dechert, 1983; Ellis, 1997). Interference is a condition when the rules of speakers’ native language (L1) influences the production of target language (L2). That was happened automatically due to habit. When writing or speaking the target language (L2), second language learners tend to rely on their native language (L1) structures to produce a response. Weinreich (1953) divided the interference into three types, namely: phonological interference, grammatical interference, and lexical interference. Berthold et al. (1997) defined the phonological interference as items including foreign accent such as stress, pronounciation, intonation and speech sounds from the first language influencing the second. Grammatical interference is defined as the first language influences the second language in terms of word order, use of pronouns and determinants, tense and mood. While, lexical interference was defined as the error in transferring and changing syllable of morpheme, affixes, phoneme, and diphthong of the lexical item of the one language into another language (Dyakov, 2008). Some studies have been conducted in the area of language interference related to the second language acquisition, and almost of them found that learner’s mother tongue or first language rules influenced the production of target language in several of levels. Lekova (2010) wrote an article about the variety of language interference with its typical influence on French language learning by students. He concluded that the language interference is directly related to the place attributed to the mother tongue in the foreign language teaching system. Firdaus (2012) has done an observation about the interference of Madurese in use of English in an English course in Probolinggo. He declared that the learner was interfered his L1 (Madurese) when he spoke in English. The interference that often happened was in the form of grammatical interference and lexical interference. English sentences and word formation they said were interfered by the structure of Madurese. In the writer’s experience in her Senior High School, her English teacher was also a Madurese native speaker. The language used by the teacher during interaction in the classroom sounded complicated because he tended to translate the language rules from Madurese to English. This made the students confused and did not understand what the teacher was talking or asking about. This example above has proven that the interference of mother tongue or first language can affect the second language acquisition. This language interference may occur because Madurese and English are distinctly different. Madurese language has a distinctive characteristic whether in its intonation, stress or speech sounds which are very different from another language including English. Fatah (2007) has observed the spoken English by Madurese Senior High School students. Then, based on his observation results, he found that the students faced some problems in stress, intonation pattern and pronunciation of their mother tongue (Madurese) interfered their spoken English. Madurese is famous with its intonation characteristic that is swaying; high pitch, suddenly low tone, and long-rising tone. Madurese also has striking differences from the other languages. This language is considered as unique language, especially in structure and syntax. Madurese and English have much distinction, especially in the term of Functional Sentences Perspective. Haq and Damanhuri (2013) declare that the third person pronoun which is usually used in English, such as “it”, “he” or “she”, does not exist in Madurese. Madurese people prefer to use “jiyah”, “roah” or mention his/her proper name. Another differences also occur in the question word formation. According to Davies (2003), the question word formations of Madurese are special. The Madurese people usually placed the WH-questions in the middle or in the end of sentence. Meanwhile, the correct structure of interrogative sentence in English, the question words are always placed in the beginning of sentence. Based on the fact above, the writter was curious to analyse the case of first language interference deeply. This research, therefore, attempts to discuss language interference with special reference to the Madurese language, which can affect Madurese English teacher’s talk during the classroom discourse. In addition, the research also investigated types of interference influenced teacher’s talk and identified how the students respond to the teacher’s talk that was interfered by the teacher’s Madurese. METHOD This study has been undertaken to find out whether there was the influence of the interference of teachers’ first language to the teacher-talk in classroom discourse, and also how its effect on learners’ language learning. Based on the objectives, the researcher decided to describe it by using words. In other words, the research was conducted in qualitative research approach. The appropriate research method for this study was the descriptive qualitative research. The descriptive method, which is a method that describes how the things really happen, was considered as appropriate method for this research because the researcher would explain the problem further and focuses on particular subjects. This research was a case study. Young (2009) states qualitative approaches have been used in a number of recent studies, especially in a case study which involves collection of detailed information about a particular case, such as; a learner, a small group of learner, teacher, or classroom. The reasons above became consideration why the researcher used descriptive qualitative method to conduct this study. The research was held in one of Senior High Schools in Bangkalan. This school was chosen because the research objects that writer needs to be observed were available, it had some teachers with Madurese background and the students tended to use bilingual languages; Bahasa and Madurese, as their daily language. It made the researcher easier to observe the case. In this research, an English teacher in one of Senior High Schools Bangkalan was the subject. He was 35 years old and has been an ELT teacher for more than ten years and absolutely has tonnes of teaching experience. He graduated from State University of Malang. This teacher has heavy Madurese accent because he is from one of rural area in Madura, so it may he uses Madurese in almost his daily activities. Moreover, this research only focused on Madurese interference in the teacher-talk during classroom discourse. Other subjects of this research were the students taught by the teacher. Because students’ learning needs were considered in this study, interview was used as a necessary research tool in order to get more complete and detailed data. There were 19 students in a class, consisted of 15 female and 4 male students. However only 5 students, as samples, who were going to be interviewed related to the teacher-talk that was interfered by first language (Madurese) used by the teacher. The data in this study were taken from utterances spoken by the teacher-talks that were used in classroom discourse. That was noted by using audio recorder and observation sheet. The whole process of teaching was recorded and transcribed to reflect what actually happened in classroom and it would be an authentic data to investigate learner’s preference towards teacher talk and their evaluation about their teachers’ talk. Other source of data was gotten from the interview result. The interview was formed in unstructured interview and also free opinion. It was addressed to some students who were taught by that teacher. It was done to bring out whether the students comprehend the instructions or explanation delivered by the teacher. For observation instruments, the researcher used an audio recorder and observation sheet. The researcher attended the class and recorded all the teacher and students interaction during the teaching learning process. Observation sheets were used for taking a note all information about how the classroom discourse is running. It helped the researcher to record the data or findings everything occurred in the class, in order to collect some information that were needed. During the observations, the researcher asked some questions to the students related to their understanding about the instruction or explanation delivered by the teacher. From the student’s answer, indirectly, could be identified whether the interfered utterances used by the teacher were understood by students or not. The utterances of teacher’s talk in classroom and student’s statements in the recording were transcribed. Then, the transcription of recording was analysed to find out whether the teacher’s first language (Madurese) interferes the use of second language in her teacher-talk. According to Richards (2003), the researcher can produce an adequate transcription for collecting and analysing the spoken interaction. In addition, for describing the phonological interference produced by the teacher; such as pronounciation and intonation, the researcher used the suprasegmental transcription. After all data were collected, the teacher talk was analysed with regard to the three research questions which the study set out to address. For the research questions, the researcher gained the data from observing and taking note how the class was running. To answer the research question number one, firstly, the researcher noted the utterances used by teacher in the feature of teacher talk and analysed which utterances were interfered by the teacher’s native language. The second research question would be answered by identifying what types of interference those are. The types of interference was grouped based on the theory from Weinreich (1953) which devided the interferences into three types, namely: grammatical interference, phonologial interference, and lexical interference. Meanwhile, the answer of last question would be gotten from analysing the students’ response during teaching learning process and the result of interview. The interview was done informally. The researcher gave several questions to some students about the teacher’s explanation or instruction during the teaching learning process. From this interview result, the researcher would get some information about students’ comprehension toward teacher’s talk. FINDINGS AND DISCUSSION After doing close examination to the transcript, the following features were found in the teacher talk performed by the English teacher during the classroom discourse. The researcher found that from fourteen features listed on SETT framework in Walsh (2006) there are only eleven features of teacher talk performed by the teacher, those are: scaffolding, direct repair, content feedback, confirmation check, extended wait-time, extended learner turn, teacher echo, extended teacher turn, turn completion, display questions and referential questions. However, not all teacher talk features were influenced by Madurese interference. The Madurese interferences were dominantly detected in the certain teacher talk features which were mostly used by the teacher and gave the teacher chance to take up a major portion of talk in classroom interaction, such as: extended teacher turn, extended wait time, content feedback, confirmation check, referential question and display question. The process of its occurrence was the teacher tends to transferred Madurese language rules into the English in his talk, especially when the teacher delivered questions whether it was referential question or display question. The table below shows the examples of utterance used by the teacher which influenced by Madurese interference found in referential and display question. Extract 1 T: Your school in where when Junior High School? S: Hah? Ya I was Junior high school a year ago, Sir. T: No no..emm..I mean where did you study in Junior High School? S6: Oooo... in Junior High School 2 Bangkalan . T: Before month February, month what that? Ss : err... T : Iya.. before February is?? Extract 2 Ss: Ooo.. January, Sir. From the extracts above, it was apparent that the Madurese interferences did exist when the teacher delivered those referential question (extract 1) and display question (extract 2). Referential questions are genuine questions which those answers are not known by the questioner since the responses given change from person to person. Those are needed to gain the students’ opinion related to the teacher questions or class discussion. From the example above, it was apparent that the Madurese interferences did exist when the teacher delivered those referential questions. Most of referential questions were interfered by Madurese in its structure (grammatical interference) and intonation (phonological interference). Although the language used was English, but the interrogative structure was simply Madurese. The error of word orders also caused the different intonation. The intonation used by the teacher when he expressed the interrogative sentences was like the way he expressed in Madurese intonation. Meanwhile, the extract 2 above is an example of display question used in teacher’s talk. Display questions were identified when the teacher gave question about holiday in this week. In researcher opinion, the point worth making in this occasion means that the teachers want to invite the students to participate in the classroom discourse. By asking some display question, the teacher can dig out students’ understanding and memorization about the knowledge they already know. The language interference in table 4.2 above was not much different from interfered utterances in referential questions. The teacher seemed to directly translate the interrogative sentence from Madurese to English in word by word. It was shown from the inappropriate placement of wh-question in interrogative sentence. This interfence is included in the grammatical interference type. According to Ellis (1994), an error of producing target language occurs as a result of interference when learners transferred their native language habit into second language. Both the similarity and difference between L1 and L2 may lead to first language transfer and it occurs inevitably, so that every second language learner is prone to have his first language interference in producing the target language, no exception for a teacher. It must be considered that every second language speaker has different level of competence and ability in expressing an idea. The lack of second language mastery is also one of factor of interference (Milroy and Wei, 1995). But somehow, the teacher intentionally used the Madurese interference; such as in his intonation and word-using, to amuse or make a joke with his students. Following Weinreich (1953) who divided the language interference into three types, namely grammatical interference, phonological interference and lexical interference. These three types of language interference were never absent in every meetings during the observations. The grammatical interference occurred when the teacher adopted the grammar structure of Madurese language to English. For instance: The example of teacher’s utterances (Madurese Structure) The correct structure of English S V N (1) you know juvenile V Qw delinquency that means what? (Be’en taoh “juvenile delinquency” jiah artenna apah?) Adv. Phrase N (2) Before month February, month Qw N what that? (sabellumma bulan Pebruari, bulan apah jiah?) Do you know what the meaning of juvenile delinquency? What is month before February? From the table above, we can clearly see that the grammatical interference occurred in the teacher’s utterances. In the example 1 and 2, the utterance structures were interfered by Madurese structure although the language used by the teacher was English. Both of those utterances were the display questions which were delivered in the teacher talk during classroom discourse. The teacher seemed to translate the interrogative sentence directly from Madurese to English. Mostly Madurese people placed the question word in the middle or in the end of sentence; it has already been their speech habit and came out unconsciously. The second type of interference that was often found in teacher’s talk during the observations was phonological interferences The distinctive characteristic of accent between Madurese and English; such as its intonation, stress or speech sounds, raised the difficulty in second language acquisition. These differences will cause negative transfer or interference, which is called phonological interference. Sometimes the teacher unconsciously spoke in Madurese intonation which absolutely different from English intonation should be spoken, for the Madurese intonation was swaying; high pitch, suddenly low tone, and long-rising tone. The examples were provided below: Do you still reme~m ber last meeting I asked you to do what? Madurese English teacher’s intonation: The Intonation of yes-no question in English should be Do you still remember last meeting what I asked you to do? The intonation of yes-no question in English should be rising in the end of sentence (Jones, 1950). However, the intonation used by the teacher when he expressed yes-no question was like the way he expressed in Madurese intonation, such as the example above. And for lexical interference, it was shown when the teacher used formation of non-existing lexical items. It was described in the example below: Extract 3 1) S : I want to hang out with Ruri to the Bangplaz on holiday tomorrow Sir. Ss : Wuuiii..... T : Ooo... You will spend your holiday by king-walking with Ruri yeh! Who want to join them? Ha ha.. Reduplication (Verb): king-walking à lan-jhalan [lən-jhələn] à take a walk The word “king-walking” in the extract 3 above was meant take a walk in English. This is kind of lexical interference dealed with reduplication Verb which is usually used in Madurese. In Madurese does exist in verb while not in English, for example: bhuk-rembhuk à discussing, bu-dhabu à talking. The teacher seemed that he wanted to make a joke or amuse the students by saying this kind interfered word (king-walking) intentionally, while the student understood what the teacher intended. Based on the findings, it was noticed that those three types of interference occurred, since the Madurese language has distinctive characteristics of language rule. However, the type of interference which mostly influenced the teacher’s talk was grammatical interference and phonological interference. According to Berthold et al. (1997), grammatical interference is defined as the first language influencing the second in terms of word order, use of pronouns and determinants, tense and mood. The grammatical interferences mostly found when the teacher produced interrogative sentences. Moreover, the Madurese interference often found in the using of third person singular. This is similar to what Haq & Damanhuri (2013) state, in that Madurese language does not know the third person. Madurese people prefer to use proper name or the word “roah”or “Jiah”. The phonology interference is related to the matters of phonology of the speaker’s native language interferes the use of target language. When the speakers are speaking a foreign language they seem to use sounds and sound patterns that were familiar with their mother tongue, objectively, rather than sounds it in the way how the native speakers speak. Avery and Ehrlich (1992) supported the idea that the learners will directly transfer their L1 sound patterns into the second language when they are not able to produce L2, and this transfer is likely to cause an error. Meanwhile, the last result to be discussed was got from the students’ responses during the classroom interaction and their statement in the interview. This discussion would give answer to the last research question. After investigating the findings, the researcher concluded that the first language interferences that were shown by the teacher gave effect to the student’s understanding toward the teacher’s talks. Most of students could not understand or catch well what the teacher question or explanation. It was proven when the students gave incorrect responses and also, sometimes, they were silent when the teacher asked questions using the utterances which interfered by Madurese language. Except that, the teacher’s mistake in pronouncing a word also affected the student’s comprehension, they would imitated that. As Weddel (2008) mentioned that the teachers’ talk always becomes their essential realia. Thus, somewhat, the students will imitate every single word the teacher said and it will be a new information or knowledge that the students keep in their memory as an input. CONCLUSIONS Based on the through elaboration and discussion upon the data on the fourth chapter, three conclusions can be drawn from this study. First, some Madurese interferences were found in English teacher’s talk in a Senior High School Bangkalan. Some utterances in some teacher talk features contained Madurese interference in all language levels; whether in grammatical, phonological and lexical. The teacher tends to transferred Madurese language rules into the English in his talk, especially when the teacher delivered questions whether it was referential question or display question. Second, it was also found that the types of interference mostly occurred during the observations was grammatical interference. Lastly, the existence of first language interference in the teacher’s talk gave effect to the student’s understanding toward the teacher’s talks. Most of students could not understand or catch well what the teacher question or explanation which was shown from the students’ responses. It happened because the language used by the teacher sounded confusing. REFERENCES Avery, P. & Ehrlich, S. (1992). Teaching American English Pronounciation. Oxford, England: Oxford University Press. Berthold, M. et al. (1997). Bilingualism & Multiculturalism: Study Book. Distance Education Centre, Universty of Southern Quessland: Towoombaa. Dulay, H., Burt, M. & Krashen, S. (1982). Language Two. New York: Oxford University Press. Davies, W. D. (2003). Extreme Locality In Madurese WH-questions. Syntax 6(3): 237-259. Davies, W. D. (1954). A Grammar of Madurese. New York: De Gruyter Mounton. Ellis, R. (1997). Second Language Acquisition. Oxford: Oxford University Press. Ellis, R. (1994). The Study Of Second Language Acquisition. Oxford: Oxford University Press. Fatah, A. C. (2007). Spoken English by Madurese Senior High School Students. Unpublished S-1 Thesis. State University of Surabaya. Firdaus, A. Y. (2012). Madurese Interference in the Use of English by the Students of Foreign Language Development Institute, Probolinggo, East Java. Unpublished S-1 Thesis. State University of Surabaya. Haq, D. D., & Damanhuri, A. (2013). Code-Mixing And Code Switching Toward English Use At Pondok Pesantren Nurul Jadid Paiton – Probolinggo. Language Horizon 1(1): 3-15. Jones, D. (1950). The Pronounciation of English. London: Cambridge University Press Lekova, B. H. (2010). Language Interference And Methods Of Its Overcoming In Foreign Language teaching. Trakia Journal of Sciences 8(3): 320-324. Milroy, L., & Wei, L. (1995). One Speaker, two languages: cross-diciplinary perspectives on code-switching. Cambridge: Cambridge University Press. Parrish, B. (2004). Teaching Adult ESL A Practical Introduction. New York: McGraw Hill. Richards, K. (2003). Qualitative Inquiry in TESOL. Birmingham: Language Studies Unit Aston University. Walsh, Steve. (2006). Investigating Classroom Discourse. New York: Routledge. Weddel, K.S. (2008). ESL Teacher Language (Teacher Talk) For Effective Classroom Interactions: Independent Study Course For Teachers of Adult English as a Second Language. Colorado: Northern Colorado Professional Development Center. Weinrich, U. (1953). Language in Contact Finding Problem. The Hague: Mounton. Young, Richard F. (2009). Qualitative Research. Madison: University of Wisconsin.